Gluten Related Disorders: People Shall not Live on Bread Alone - Carlo Catassi (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Once upon a time, gluten was not part of the human diet, and therefore, there were no gluten-related disorders. With the advent of agriculture 10,000 years ago, the introduction of gluten-containing grains in the human diet created conditions for human diseases related to gluten exposure. These diseases, including celiac disease, non-celiac gluten sensitivity, and wheat allergy, have distinct pathophysiological mechanisms, serological markers, and long-term treatments, but similar, often overlapping clinical presentations. Though current research strives to clarify the boundaries between these entities, their differences can be difficult to distinguish. For a very long time, awareness of these disorders has been limited and, therefore, the epidemiology of gluten-related disorders has been a "work in progress". New epidemiological studies have revealed that gluten-related disorders are not limited to European regions; rather, they are present worldwide. After centuries of neglected attention to celiac disease and other forms of gluten reaction, now we are observing another interesting phenomenon that is generating great confusion among health care professionals. Nearly 25% of Americans (many more than the projected 3 million celiac disease (CD) patients in the U.S.) are reducing or cutting gluten from their diets. This remarkable trend in the general population reflects the misconception that gluten can be harmful for everybody and, therefore, should be avoided to stay healthy, to lose weight, or even to prevent severe diseases. This Special Issue Book of Nutrients contains contributions from leading experts in the field of gluten-related disorders that will help dissipate this confusion by sharing their evidence-based science, which will help the reader to distinguish facts from fantasies.